Modeling of SOI-based MRR by coupled mode theory using lateral coupling configuration - N V Visvanathan, P. Susthitha Menon; Haroon, Hazura; Majlis, Burhanuddin Yeop; Abdul Razak, Hanim; Bidin, Mardiana; Lilik Hasanah; Budi Mulyanti; Dadin Mahmudin; Goib Wiranto (2010)
We present the modeling of a first order waveguide-coupled microring resonator (MRR) by coupled mode theory (CMT) using transfer matrix model. The design topology is based on the lateral coupling configuration and single mode propagation which is integrated on a Silicon-on-Insulator (SOI) platform. Performance parameters including Free Spectral Range (FSR) and Quality Factor (Q-factor) are investigated. For verification, we compare these results with the results obtained from the Finite Difference Time Domain (FDTD) commercially available software. We found that both results agree well with each other.